The comparative study of social action: what you must and what you can do to align with a prior speaker - Zinken, Jörg (Research on language and social interaction, 2020)
This article makes an empirical and a methodological contribution to the comparative study of action. The empirical contribution is a comparative study of three distinct types of action regularly accomplished with the turn format du meinst x (“you mean/think x”) in German: candidate understandings, formulations of the other’s mind, and requests for a judgment. These empirical materials are the basis for a methodological exploration of different levels of researcher abstraction in the comparative study of action. Two levels are examined: the (coarser) level of conditionally relevant responses (what a response speaker must do to align with the action of the prior turn) and the (finer) level of “full alignment” (what a response speaker can do to align with the action of a prior turn). Both levels of abstraction provide empirically viable and analytically interesting descriptive concepts for the comparative study of action. Data are in German.